Observed and Future Spatiotemporal Changes of Rainfall Extreme Characteristics and Their Dynamic Driver in June-August Season over Africa - Teshome, Asaminew; Jie Zhang; Demissie, Teferi Dejene; Qianrong Ma (Scientific Research Publishing, Inc., 2022)
Climate change has increased extreme events over globe and the most robust occurrences of concurrent drought and floods have become more common in Africa. This study focuses on the observed and projected analysis of rainfall extremes of consecutive dry day (CDD) and maximum monthly five day precipitation (RX5day) from Expert Team on Climate Change Detection and Indices (ETCCDI) in June-August season over Africa. The daily CORDEX Africa, reanalysis and CRU datasets were analyzed for extreme trends under RCP4.5 and RCP8.5 scenarios for the periods of 1980 to 2100. The spatiotemporal variability, trend, and magnitude of JJA seasonal rainfall performance exhibits a significant decreasing tendency over Eastern Africa compared to West Africa. The observed results of consecutive dry day (CDD) reveal that increasing trend and moreover RX5day shows that promising positive trend. Both rainfall extremes are influenced by the combined effect of large scale indexes and appear to be correlated negatively and positively with ENSO, NAO and AO. The CORDEX ensemble mean projections of JJA seasonal rainfall performance show a widespread significant change and the first mode of EOF depicts that 13.8% and 24.9% under the RCP4.5 and the highest variability is under RCP8.5 scenario. The projected CDD extreme exhibit an increasing trend in the coming periods and the percentage change revealed that increasing from 25.11%, 28.02% over West and 26.49%, 31.66% East Africa under RCP4.5 and RCP8.5 scenarios respectively. This situation will exacerbate increasing of frequent and intensified drought extremes over Africa. Additionally, the future RX5day indicated that mixed trend and revealed that increasing 3.72%, 2.54% over West and decreases -16.12%, -22.47% over East Africa under RCP4.5 and RCP8.5 respectively. Generally, rainfall extremes of CDD are projected to increase and RX5day shows a mixed trend in the coming periods over Africa and calls for further verification by using high resolution datasets.